PRODUCCIÓN DE AGUA ELECTROLIZADA PARA ELIMINACIÓN DE MICROORGANISMOS EN LECHUGA - Chaves, Gustavo Adolfo; Departamento de Microbiología, Facultad de Ciencias, Pontificia Universidad Javeriana, Bogotá (2004)
We carried out the building of one electrolytic cell for production of electrolysed oxidizing (EO) water. We frequently tested pH and available chlorine (residual chlorine). The efficacy of EO water (14 ppm available chlorine and pH 2,7 +/- 0.2) was evaluated with the strain E.coli ATCC 25999 (experiment in vitro). After, to obtain the culture in stationary  phase (9 hours) this was subdue to water EO treatment under different exposition times (0, 2, 5, 10, 15 and 20 minutes). The maximum log  reduction (11,3 Log 10 CFU/ml) occurred with 20 minutes of exposition. We used lettuce for experiment “In vivo”, we took 10 grams of lettuce  and it were submerged in 200 ml EO water during 20 minutes. We did counts mesophilics bacterial, total coliforms, faecal coliforms and moulds and yeast. The results indicated one total elimination of  coliforms faecal and total, one log reduction ( 4.16 Log 10 CFU/ml) for  mesophilics bacterial and log reduction (3.15 Log 10 CFU/ml) for  moulds and yeast.We probed that the utilization of water EO over contaminated lettuce has microbiocidal effect significative statistically (p:0.0001). We believe that the use this EO water could be a really good option for the clean and disinfections process over vegetables.